2014
DOI: 10.1007/s00345-014-1291-8
|View full text |Cite
|
Sign up to set email alerts
|

Peri-procedural povidone-iodine rectal preparation reduces microorganism counts and infectious complications following ultrasound-guided needle biopsy of the prostate

Abstract: Peri-procedural PIRP decreased microorganism colony counts and effectively reduced infectious complications following TRUS PNB. This safe, cheap, and simple strategy may be a reasonable alternative to systemic or targeted antibiotic therapy to reduce post-biopsy infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…From metaanalysis of seven controlled trials (n = 2,049) of rectal disinfection using PIRP prior to TRUBP, significant reductions in fever, bacteruria and bacteraemia (RR 0.31; 95% CI 0.21 -0.45) regardless of prophylaxis used have been reported 88 . Recent retrospective studies further report significant reductions in infectious complications when PIRP was used 89 , as well as in conjunction with targeted prophylaxis 90 . However, a randomised controlled trial of prophylactic povidone-iodine use demonstrated insignificantly reduced complication rates (2.6%) compared with control (4.5%), in a study that is likely to have been underpowered 91 .…”
Section: Rectal Disinfectionmentioning
confidence: 99%
“…From metaanalysis of seven controlled trials (n = 2,049) of rectal disinfection using PIRP prior to TRUBP, significant reductions in fever, bacteruria and bacteraemia (RR 0.31; 95% CI 0.21 -0.45) regardless of prophylaxis used have been reported 88 . Recent retrospective studies further report significant reductions in infectious complications when PIRP was used 89 , as well as in conjunction with targeted prophylaxis 90 . However, a randomised controlled trial of prophylactic povidone-iodine use demonstrated insignificantly reduced complication rates (2.6%) compared with control (4.5%), in a study that is likely to have been underpowered 91 .…”
Section: Rectal Disinfectionmentioning
confidence: 99%
“…Perhaps, a convincing argument for the use of preprocedural rectal povidone-iodine preparation comes from a retrospective study by Gyorfi et al 35 They utilized a slurry consisting of 10% povidone-iodine solution mixed with lidocaine jelly. All patients received standard prophylaxis, which included either a 3-day regimen of ciprofloxacin or trimethoprim sulfamethoxazole.…”
Section: Strategies For Preventing Pnb-related Infectionsmentioning
confidence: 99%
“…Povidone-iodine is an easily accessed, cheap antiseptic solution commonly used to clean the surgical field for daily surgical procedures. As it is safe for mucosa, it is commonly used during gynecological and colorectal surgery [25]. A study by Park et al divided 408 patients undergoing biopsy into two groups of patients either administered povidone-iodine in suppository form for intestinal preparation or not.…”
Section: Discussionmentioning
confidence: 99%